Rab GTPases are essential for membrane trafficking‐dependent growth and pathogenicity in Fusarium graminearum. (11th August 2015) - Zheng, Huawei; Zheng, Wenhui; Wu, Congxian; Yang, Jie; Xi, Yang; Xie, Qiurong; Zhao, Xu; Deng, Xiaolong; Lu, Guodong; Li, Guangpu; Ebbole, Daniel; Zhou, Jie; et al.
Summary: Rab GTPases represent the largest subfamily of Ras‐related small GTPases and regulate membrane trafficking. Vesicular transport is a general mechanism that governs intracellular membrane trafficking along the endocytic and exocytic pathways in all eukaryotic cells. F usarium graminearum is a filamentous fungus and causes the devastating and economically important head blight of wheat and related species. The mechanism of vesicular transport is not well understood, and little is known about Rab GTPases in F . graminearum . In this study, we systematically characterized all eleven FgRabs by live cell imaging and genetic analysis. We find that FgRab51 and FgRab52 are important for the endocytosis, FgRab7 localizes to the vacuolar membrane and regulates the fusion of vacuoles and autophagosomes, and FgRab8 and FgRab11 are important for polarized growth and/or exocytosis. Furthermore, both endocytic and exocytic FgRabs are required for vegetative growth, conidiogenesis, sexual reproduction, as well as pathogenesis and deoxynivalenol metabolism in F . graminearum . Thus, we conclude that Rab GTPases are essential for membrane trafficking‐dependent growth and pathogenicity in F . graminearum .